2020
DOI: 10.1186/s13063-020-04286-2
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure to improve sleep quality of older people in residential aged care: a randomised controlled trial protocol

Abstract: Background: Sleep disturbance in older people is an important health issue that is associated with many other health problems. Effective interventions are required to address sleep problems in this group. Acupressure has been suggested as a potential therapeutic technique to improve sleep. The aim of this study is to evaluate the effects of an acupressure intervention on sleep quality, anxiety, depression, and quality of life among older persons in residential aged care facilities within an Australian context.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
9
0
4
Order By: Relevance
“…However, the path through which sleep quality affects medical staff suffering from IBS requires further research. Studies have shown that aerobic exercise and appoint massage can improve sleep disorders [30,31], hospital unions can organize these activities to improve the sleep conditions of employees.…”
Section: Discussionmentioning
confidence: 99%
“…However, the path through which sleep quality affects medical staff suffering from IBS requires further research. Studies have shown that aerobic exercise and appoint massage can improve sleep disorders [30,31], hospital unions can organize these activities to improve the sleep conditions of employees.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to recruitment rates for other pilot and feasibility studies of intradialytic interventions (Thompson et al, 2016), suggesting that the provision of interventions during haemodialysis treatment is a highly acceptable mode of delivery. While there is some evidence that people may be sceptical about the benefits of reflexology and other complementary medicines and that this might have an impact on the uptake of such interventions (Hmwe et al, 2020), this study has established that there is enough interest and engagement to support evaluation within a definitive trial.…”
Section: Discussionmentioning
confidence: 82%
“…Many trials measuring the effect of an intervention on sleep quality do so in specific groups of people, e.g. cancer patients [ 31 ], older adults [ 32 ] or those with a history of mental health diagnosis [ 33 ]. The Reading Trial included a large, diverse sample of participants.…”
Section: Discussionmentioning
confidence: 99%